Pengaruh Stres Akademik terhadap Kesejahteraan Psikologis Mahasiswa Semester Akhir yang Terlambat Lulus - Gisela, Evangelica Shane; Kinkie, Emmanuella Anastacia; Sabbilla, Auliana; Subroto, Untung (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Academic stress is a common problem faced by final semester students, especially those who experience delays in graduation. This study aims to analyze the relationship between academic stress and psychological well-being in final semester students who experience delays in graduation. Using a quantitative approach with a correlational design, this study involved 100 students who were purposively selected. Data were collected using a questionnaire that included an academic stress scale and a psychological well-being scale. The results showed a significant negative correlation between academic stress and psychological well-being, with a correlation coefficient of -0.814 at a significance level of 0.01 (p < 0.001). Based on these results, it is recommended that educational institutions provide additional support to assist students in managing academic stress and improving their psychological well-being.